CONTENT-BASED APPROACH IN TEACHING TECHNICAL AND SCIENTIFIC TRANSLATION - Radetska, Svitlana; Mazur, Olena (The Modern Higher Education Review, 2023)
This paper deals with content-based approach to translating scientific and technical literature, vital for gaining effective translation competence in specialized translation. Central to this research is the development of a methodology for selecting appropriate texts for training future translators. The study emphasizes the importance of choosing authentic texts that are modern, diverse, and relevant to various fields of science and technology, sourced from printed publications, electronic resources, and materials commonly encountered in professional practice. The research underscores the significance of thematic alignment, terminological richness, and the presence of lexical, grammatical, stylistic, and pragmatic challenges in the texts chosen to enhance students' translation skills. The paper outlines a systematic approach to teaching translation skills, emphasizing a content-based strategy that focuses on communicative necessity and thematic relevance. This methodological study on scientific and technical texts’ selection is the first in a series of similar ones aimed at creating an effective learning structure, which will ultimately enhance the competence of future professionals in this field.